Comparison of the Effect of 8 Weeks of Land Exercise Therapy and Hydrotherapy on Functional Activities of Elderly Women with Knee Osteoarthritis - Azra Sadat Etesami; Vahid Zolaktaf; Hamed Esmaeili (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Knee osteoarthritis is one of the most common musculoskeletal problems in older adults. Pain, stiffness, tenderness, decreased muscle strength and joint range of motion, impaired proprioception, and balance problems lead to impaired physical function, making the person incapable of performing functional activities. Therefore, it is necessary to use strategies to control and reduce the complications of this disease and improve the daily functional activities of patients. This study aims to compare the effects of land-based exercise and hydrotherapy on functional activities in older women with knee osteoarthritis. Methods & Materials Fifty-four female patients with knee osteoarthritis aged 60-69 years (Mean height:159.96 ±5.53 cm, mean weight:76.93±9.50 kg) were selected using a convenience sampling method and randomly divided into two groups of land-based exercise and hydrotherapy. The interventions were performed for 8 weeks. To evaluate the patients' functional activities, timed up & go test, 30- second chair stand test, 40-meter fast-paced walk test, stair climb test, and 6-minute walk test were used. Repeated measures analysis of variance was used for data analysis in SPSS v. 26. Results Both land-based exercise and hydrotherapy caused significant changes in the scores of functional tests (P≤0.05). The difference between them was not significant (P≥0.05), which indicates their same effects. Conclusion Both land-based exercise and hydrotherapy can improve the performance of older women with knee osteoarthritis in timed get up & go test, 30-second chair stand test, 40-meter fast-paced walk test, stair climb test, and 6-minute walk test. These two methods are recommended based on the conditions of each patient.